MENINGKATKAN HASIL BELAJAR SISWA PADA PEMBELAJARAN IPA DENGAN MENGGUNAKAN MODEL DISCOVERY LEARNING DI KELAS V SD NEGERI 36 SUNGAI LIMAU - Ratnasari, Depi; Yuliar, Yuliar; Muhammadi, Muhammadi (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2014)
The purpose of this research is to describe to improve science learning by using Model Discovery Learning in class V SDN 36 Sungai Limau Kabupaten Padang Pariaman. The type of this research is Classroom Action Research (PTK) and using qualitative and quantitative approach. The subjects of this study are students of grade V SDN 36 Sungai Limau Padang Pariaman, which amounts to 12 people. This study consists of 2 cycles. The research procedure consists of four stages: (1) planning, (2) implementation, (3) observation, (4) reflection. The results of this study using inquiry methods in Elementary School. The result of RPP assessment using Discovery Learning Model in cycle I is 73,21% and in cycle II become 92,85%. Teacher aspect in cycle I 69,3% increase in cycle II become 95,83%. Aspects of students in the cycle I 70.83% to 91.30% in cycle II. The average haisl studied students in cycle I 66.46 and increased in cycle II to 83.75.Keywords – Understanding of sciences concepts, discorvery learning method